Goosebumps SlappyWorld : Night of the Squawker - Book 18 - Stine, R. L. (New York, NY : Scholastic Inc., 2023)
"Beak-a-boo, it sees you! Cooper Klavan and his sister Anna are fishing with their parents at a woodland pond when they come across an injured bird. Anna, a huge animal lover, insists on taking it home to rehabilitate. But the bird really does not want to be rescued. It bites Anna, and scares Cooper. Soon, Anna is behaving very strangely. She's perching high up in trees, gathering sticks to hide in her room, and refusing to eat eggs-- once one of her favorite foods. Cooper doesn't want to jump to any conclusions, but his sister seems to be going to the birds."--
Keywords: Birds -- Juvenile fiction; Siblings -- Juvenile fiction; Monsters -- Juvenile fiction; Birds -- Fiction; Siblings -- Fiction; Monsters -- Fiction; Juvenile Horror fiction